Significance of Undissected Retromaxillary Air Cells as a Risk Factor for Revision Endoscopic Sinus Surgery. Issue 6 (September 2016) - Kuan, Edward C.; Clair, Jon Mallen-St.; Frederick, John W.; Tajudeen, Bobby A.; Wang, Marilene B.; Harvey, Richard J.; Suh, Jeffrey D.
Background: Retromaxillary air cells (RMC) are posterior ethmoid cells that separate the maxillary and ethmoid sinuses. The clinical significance of these cells in contributing to revision functional endoscopic sinus surgery (FESS) is unknown. Objectives: To investigate the prevalence, anatomic dimensions, and radiographic characteristics of RMC in patients with recalcitrant chronic rhinosinusitis after previous FESS. Methods: A retrospective review of patients who underwent revision FESS at a tertiary medical center between January 1, 2012, and December 31, 2014. Computed tomographies of patients who underwent revision FESS, including posterior ethmoidectomies, were reviewed. Each side of the scan was assessed for residual RMCs. The radiographic dimensions and Lund-Mackay (LM) scores of these cells were recorded. Results: Sixty-nine patients who underwent revision FESS were identified. The median age of the patient population was 51 years (range, 21–79 years). Forty-two percent of the patients had nasal polyps. The mean number of previous FESS was 2 (range, 1–10). Incompletely dissected RMCs were identified in 101 of 138 analyzed sides (73%), despite documented previous posterior ethmoidectomies. Sixty-five percent of RMCs had an LM score of >1; RMCs of patients with polyps were more likely to have an LM score of 2 (p = 0.049). There was a significant correlation between the number of previous FESS procedures and whether the RMCs had been dissected (p = 0.010). There also was a significant correlation between RMC height and the number of previous FESS procedures (p = 0.015). Conclusion: RMCs seemed to often be undissected during primary FESS and, thus, were commonly encountered in revision FESS. The majority of analyzed cells in this cohort demonstrated an LM score of >1, which indicated that these cells frequently harbor residual diseased mucosa that may contribute to the need for revision surgery.